The Production of IF(B3Π) in the 248 nm Laser Photolysis of Fluorine/Alkyl Iodide Mixtures. Issue 4 (1988) - Raybone, D.; Watkinson, T. M.; Whitehead, J. C.; Winterbottom, F.
Abstract : Sustained visible emission in the region 440–850 nm from the B→ X system of IF is observed when a gas phase mixture ( 0.5 mbar) of an alkyl iodide with F2 in He is photolysed at 248 nm by a KrF laser. The total intensity and decay rate of the IF(B) emission is a strong function of the identity of the alkyl iodide and can be correlated with the 248 nm photon yields for the production of I *( 2 p 1/2 ). The half-lives for the IF(B) decays range from 5 μ s for t -C4 H9 I to 770 μ s for n -C3 F7 I. Decay curves for the I *( 2 p 1/2 ) concentrations are also measured by atomic fluorescence. The mechanism for IF(B) formation in these systems is discussed and it is suggested that IF(B) is produced either by a recombination process involving I * and F atoms or by multistep collisional excitation of ground state IF(X) by I *. The F atoms can be produced following the photolysis pulse by the reaction of the alkyl radical with molecular fluorine and IF(X) can result either from the reaction of F atoms with the alkyl iodide or from a dark reaction between molecular fluorine and the alkyl iodide.